Health Insurance and Demography: The Russian Case - Stefan Fetzer; Christian Hagist; Nargiza Hahn (Albert-Ludwigs-Universität Freiburg, Institut für Finanzwissenschaft, 2005)
This paper assesses the long-term fiscal position of the Russian health insurance system using Generational Accounting, with particular attention to special factors of the health care sector. We find out that the demographic development of Russia causes a significant burden for future generations. Taking into account a form of cost pressure due to the medical-technical progress or a widen of the scope of benefits in the health care sector, we show that the burden is comparable to OECD-countries like Germany.
urn:nbn:de:bsz:25-opus-18473
Keywords: H51; I11; 330; Gesetzliche Krankenversicherung; Gesundheitsfinanzierung; Intergenerative Belastungsrechnung; Alternde Bevölkerung; Russland